Recommendations for the treatment of vulvar cancer in settings with limited resources: Report from the International Gynecological Cancer Society consensus meeting - Maluf, Fernando Cotait; Zibetti, Graziela Dal Molin; Paulino, Eduardo; de Melo, Andreia Cristina; Racy, Douglas; Ferrigno, Robson; Uson Junior, Pedro Luiz Serrano; Ribeiro, Reitan; Moretti, Renato; Sadalla, Jose Carlos; Nogueira Rodrigues, Angelica; Carvalho, Filomena Marino; et al. (Frontiers in Oncology, 2022)
ABSTRACT Introduction: Due to a scant literature and the absence of high-level evidence, the treatment of vulvar cancer is even more challenging in countries facing limited resources, where direct application of international guidelines is difficult. Recommendations from a panel of experts convened to address some of these challenges were developed. Methods: The panel met in Rio de Janeiro in September 2019, during the International Gynecological Cancer Society congress and was composed of specialists from countries in Africa, Asia, Eastern Europe, Latin America, and the Middle East. The panel addressed 62 questions and provided recommendations for the management of early, locally advanced, recurrent and/or metastatic vulvar cancer. Consensus was defined as at least 75% of the voting members selecting a particular recommendation, whereas a majority vote was considered when one option garnered between 50.0% and 74.9% of votes. Resource limitation was defined as any issues limiting access to qualified surgeons, contemporary imaging or radiation-oncology techniques, antineoplastic drugs, or funding for the provision of contemporary medical care. Results: Consensus was reached for nine of 62 (14.5 %) questions presented to the panel, whereas majority vote was reached for 29 (46.7%) additional questions. For the remaining questions, there was considerable heterogeneity in recommendations. Conclusion: The development of guidelines focusing on areas of the world facing more severe resource limitations may improve medical practice and patient care.